Facilitating Preservice Teachers’ Socioscientific Issues Curriculum Design in Teacher Education - Foulk, Jaimie; Sadler, Troy D.; Friedrichsen, Patricia M. (Innovations in Science Teacher Education, 2020)
Socioscientific issues (SSI) are contentious and ill-structured societal issues with substantive connections to science, which require an understanding of science, but are unable to be solved by science alone. Consistent with current K-12 science education reforms, SSI based teaching uses SSI as a context for science learning and has been shown to offer numerous student benefits. While K-12 teachers have expressed positive perceptions of SSI for science learning, they cite uncertainty about how to teach with SSI and lack of access to SSI based curricular materials as reasons for not utilizing a SSI based teaching approach. In response to this need we developed and taught a multi-phase SSI Teaching Module during a Science Methods course for pre-service secondary teachers (PSTs), designed to 1) engage PSTs as learners in an authentic SSI science unit; 2) guide PSTs in making sense of an SSI approach to teaching and learning; and 3) support PSTs in designing SSI-based curricular units. To share our experience with the Teaching Module and encourage teacher educators to consider ways of adapting such an approach to their pre-service teacher education contexts, we present our design and resources from the SSI Teaching Module and describe some of the ways PSTs described their challenges, successes, and responses to the experience, as well as considerations for teacher educators interested in introducing PSTs to SSI.